Decomposition and nutrient release of sal leaf litter as influenced by legume leaf litter of the sal forests (Dhaka University Journal of Biological Sciences, 2013)
Abstract not availableDhaka Univ. J. Biol. Sci. 22(2): 183-186, 2013 (July)